Pathological Mechanisms in Diabetes of the Exocrine Pancreas: What’s Known and What’s to Know - Wei, Qiong; Qi, Liang; Lin, Hao; Liu, Dechen; Zhu, Xiangyun; Dai, Yu; Waldron, Richard T.; Lugea, Aurelia; Goodarzi, Mark O.; Pandol, Stephen J.; Li, Ling (Frontiers in Physiology, 2020)
The clinical significance of diabetes arising in the setting of pancreatic disease (also known as diabetes of the exocrine pancreas, DEP) has drawn more attention in recent years. However, significant improvements still need to be made in the recognition, diagnosis and treatment of the disorder, and in the knowledge of the pathological mechanisms. The clinical course of DEP is different from type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM). DEP develops in patients with previous existing exocrine pancreatic disorders which damage both exocrine and endocrine parts of pancreas, and lead to pancreas exocrine insufficiency (PEI) and malnutrition. Therefore, damage in various exocrine and endocrine cell types participating in glucose metabolism regulation likely contribute to the development of DEP. Due to the limited amount of clinical and experimental studies, the pathological mechanism of DEP is poorly defined. In fact, it still not entirely clear whether DEP represents a distinct pathologic entity or is a form of T2DM arising when β cell failure is accelerated by pancreatic disease. In this review, we include findings from related studies in T1DM and T2DM to highlight potential pathological mechanisms involved in initiation and progression of DEP, and to provide directions for future research studies.